Overview of Commodity Interest Groups (CIGs) in North Eastern States - Pradip.K.Neog; D.Bortamuly; P. Das; B.L.Khuhly (Journal of Agricultural Extension Management, 2015)
The group and farmer led extension approaches like formation of CIGs and Farm Schools at village levels are gaining momentum under the Centrally Sponsored Scheme "Support to State Extension Programmes for Extension Reforms" which is being implemented in the country since 2005-06 including the North Eastern states. A Commodity Interest Group is a self-managed, independent group of farmers with a shared goal and interest. This study gives an overview of CIGs operating in the North East and also investigates the perceived constraints faced by the block level extension functionaries while facilitating CIGs. A questionnaire was prepared and responses received from Assam, Nagaland, Arunachal Pradesh, Mizoram Manipur, Sikkim and Meghalaya. The study reveals that majority ( 30.6%) of CIGs are involved in ’Vegetable production’ followed by ’Cultivation of Spices & Condiments’ ( 14.0%), ’Cultivation of rice’ (11.1%), ’Piggery’ (8.9%), ’Cash crops,’ (7.1%), ’Poultry’ (6.7%), ’Cultivation of pulses & oilseeds’ (6.5%), ’Fishery’ (4.3%), ’Sericulture ’ (3.8%), ’Floriculture ’ (2.4%) and ’Cultivation of banana’ (1.6%). The potentialities from the agro-ecological and socio-cultural perspective in NE states are enormous for commercial venture of spices & condiments and medicinal plants. There is a need and scope of forming Federation of Vegetable CIGs in NE states as most of CIGs in this region are engaged in vegetable production